2001
DOI: 10.1046/j.1365-2249.2001.01669.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell-binding activity of anti-U1-ribonucleoprotein antibodies in patients with connective tissue diseases

Abstract: SUMMARYIn order to elucidate the immunological properties of anti-U1-ribonucleoprotein (RNP) antibody, one of the autoantibodies detected in patients with connective tissue diseases (CTDs), we tested the endothelial cell-binding by anti-U1-RNP antibodies and epitopes on human pulmonary artery endothelial cells (HPAECs) to which the autoantibody bound. IgG fractions positive for anti-U1-RNP from patients with CTDs bound to the HPAECs. Furthermore, intact and F(ab H ) 2 IgG anti-U1-RNP purified by affinity chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…4,12,20,21 In this study, a significant difference in the EC IgG levels was found between patients with active lupus nephritis and those without nephritis (see Fig. 4).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…4,12,20,21 In this study, a significant difference in the EC IgG levels was found between patients with active lupus nephritis and those without nephritis (see Fig. 4).…”
Section: Discussionsupporting
confidence: 51%
“…1 Antiendothelial cell antibodies (AECA) or endothelial cell-binding IgG antibodies (EC IgG) have been determined in various types of autoimmune diseases associated with vasculitis. [2][3][4] AECA or EC IgG have been detected in more than 50% of patients with SLE, and its correlation with disease activity has been reported. [5][6][7][8][9] However, the results of the relationship with clinical parameters such as levels of serum complement, antinuclear antibody (ANA), anti-DNA antibody (anti-DNA Ab), and antiphospholipid antibody (APA) differed in many reports.…”
Section: Introductionmentioning
confidence: 97%
“…In MCDT, anti-RNP antibodies have been found to interact with lung tissue in ways that could mediate MCTD lung pathology [183]. Immunization of susceptible mice with RNP antigen could induce MCTD-like serologic responses and some clinical manifestations [169].…”
Section: Autoantibodiesmentioning
confidence: 99%
“…Autoantibodies in MCTD recognize intact and apoptotically modified forms of individual U1 snRNP proteins (8,9), and frequently also recognize structures composed of multiple subunits of the U1 snRNP macromolecule (10). Moreover, anti-RNP antibodies have been found to interact with lung tissue in ways that could mediate MCTD lung pathology (11). In a small series of mice, we have previously found that direct immunization of a susceptible animal with RNP antigen could induce MCTD-like serologic responses and clinical manifestations (12).…”
mentioning
confidence: 99%